AN ASSESSMENT OF TRADITIONAL UIGHUR MEDICINE IN CURRENT XINJIANG REGION (CHINA) - Ma, Zhi Qiao; Hu, Hao; He, Tian Tian; Guo, Hong; Zhang, Mao Yu; Chen, Mei Wan; Wang, Yi Tao (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The main objectives of this study were to assess the current research and development of traditional Uighur medicine in Xinjiang (China), and to evaluate the promising pharmacological products of traditional Uighur medicine for further studies. Materials and Methods: Traditional Uighur medicine data of medicine registry, patent, and academic publications was collected and analyzed. Results: Data showed that, among the registered and studied traditional Uighur medicine, the main therapeutic areas of traditional Uighur medicine focused on skin disease, urogenital disease, rheumatism and digestive system disease. The representative traditional Uighur patent medicine included the following: BaixuanXiatare Tablets, Kaliziran Tincture and Vernoniaanthelmintica Injection (Psoriasis and vitiligo); Xi-payimazibiziLiquid (prostatitis); KursiKaknaq (urinary tract infection); Tongzhisurunjiang Capsules (anti-rheumatism medicine); HuganBuzure Granules (digestive system disease). Moreover, ten Uighur herbs were widely used, including: ResinaScammoniae, Folium FumicisDentati, HerbaDracocephali, Semen AmygdaliDulcis, HerbaChamomillae, FructusPimpinellaeanisi, Cortex Foeniculi, FructusVernoniae, FructusApii, and Radix AnacycliPyrethri. Conclusion: This study concluded by indicating that traditional Uighur medicine with excellent curative effect should be screened in details for their phytochemical properties and pharmacological activity to discover new bioactive constituents.